Healthcare Providers' Interprofessional Collaboration Experience with Integrated Information System for Non-Communicable Disease Management at Primary Care in Indonesia A Qualitative Study - Akbar, M Agung (International journal of community based nursing and midwifery, 2025)
Copyright: © International Journal of Community Based Nursing and Midwifery.